Spirituality as a Mediator Between Psychological Well-Being and Life Satisfaction - Kondal, Sonali; Aswal, Tanisha; Das, Anushka (Journal of Social Science and Humanities, 2025)
Spirituality encompasses a deeply personal and subjective journey, marked by an intimate connection to forces transcending the self. A study encompassing 100 college students, equally divided between genders, delved into this realm. Employing the Spiritual Health Assessment Scale (Gaur and Sharma, 2014), Psychological Well-being (Ryff and Keyes, 1995), and Satisfaction with Life Scale (Diener et al., 1985), researchers sought to unravel the intricate interplay between spirituality, psychological well-being, and life satisfaction. Utilizing descriptive statistics, correlation analysis, and stepwise multiple regression, the data unveiled compelling insights. It revealed a significant and positive association between spirituality and both psychological well-being and life satisfaction. Furthermore, the findings illuminated spirituality's profound impact across various dimensions of life. This study offers invaluable contributions, shedding light on the pivotal role of spirituality in the lives of college students. It underscores its capacity to bolster psychological well- being and engender overall life satisfaction. These revelations hold profound implications, advocating for holistic approaches to student development. They underscore the importance of cultivating a nurturing environment conducive to spiritual growth, fostering resilience, and enriching the collegiate experience.